PRINSIP KEHATI-HATIAN BANK DALAM PEMBIAYAAN AKAD MURABAHAH TERKAIT PEMBERIAN KREDIT TERHADAP DEBITUR BERESIKO TINGGI - Nur Cahaya (2023)
The precautionary principle is a principle that emphasizes that Islamic banks in carrying out their business activities both in collecting and distributing funds to the public must comply with Law Number 10 of 1998 concerning Banking. Most of the problems in banking lie at the time of the murabaha financing contract due to the failure to apply the precautionary principle in the financing process. This study aims to examine the juridical aspects of the prudential principle of banks in financing murabahah contracts for granting credit to high-risk debtors and assessing the fair object of collateral execution. This research uses the type of normative juridical research. The results of this study indicate that there are several possibilities that occur which cause the precautionary principle not to be applied during the contract process, firstly there are internal factors where bank employees have been negligent in the contract process, secondly there are external factors, where the debtor himself is a high-risk debtor. Then the execution of the collateral object must be carried out in a fair manner, must apply the principle of legal certainty, transparency in terms and procedures for executing collateral, auctioning the value of the object according to BJOP standards, legal protection for debtors. Suggestions from this study, in carrying out the execution of guarantees, the Bank must apply the precautionary principle and conduct an assessment before financing a murabaha contract. Then the Bank must follow the applicable laws and regulations in executing the collateral object.